2021
DOI: 10.1021/acsomega.1c04699
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature Change on the Change Law of Free Radicals in Coal

Abstract: This study investigates changes in the concentration and types of free radicals in the process of coal heating, first rising and then falling. Hailar lignite, Panjiang bituminous coal, and Yangquan anthracite were selected as coal test samples. The results show that the lignite’s concentration of free radical changes during heating is greater than that of bituminous coal or anthracite. It clearly shows that lignite is more prone to spontaneous combustion. In the heating and cooling portion of the experiment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The final result of total radical content increased only slightly compared with that before cooling, because the highest content of aromatic stable free radicals was kept almost unchanged in the cooling stage. In light of the studies on EPR applications to the pyrolysis of model compounds, , these phenomena indicate that, at the initial cooling stage, the bonds of oxygen-containing heterocycles or oxygen bridges are cleaved to form central oxygen radicals because the cooling stress damages the coke structure, which is similar to the formation of free radicals in the cooling process of coal char or biochar. , The free radicals generated in the cooling stage are highly reactive. With time, most of them are annihilated, and a small part are transformed into oxygen-containing stable free radicals. ,, In this process, the aromatic skeleton supported the coke structure, and the stable free radicals did not change.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final result of total radical content increased only slightly compared with that before cooling, because the highest content of aromatic stable free radicals was kept almost unchanged in the cooling stage. In light of the studies on EPR applications to the pyrolysis of model compounds, , these phenomena indicate that, at the initial cooling stage, the bonds of oxygen-containing heterocycles or oxygen bridges are cleaved to form central oxygen radicals because the cooling stress damages the coke structure, which is similar to the formation of free radicals in the cooling process of coal char or biochar. , The free radicals generated in the cooling stage are highly reactive. With time, most of them are annihilated, and a small part are transformed into oxygen-containing stable free radicals. ,, In this process, the aromatic skeleton supported the coke structure, and the stable free radicals did not change.…”
Section: Resultsmentioning
confidence: 99%
“…This means that a large number of free radicals were generated when the sample was cooled. The phenomenon is also observed in the studies on coal char 48 and biochar. 49 According to the result of peak splitting in Figure 7, the newly generated radicals were oxygen center stable free radicals distributed on oxygen-containing heterocycles or near oxygen bridge bonds with the lowest g value.…”
Section: Evolution Of Stable Free Radicals During the Cooling Stage O...mentioning
confidence: 97%
See 2 more Smart Citations
“…Li et al [7] carried out a low-temperature oxidation experiment, grinding experiment, infrared spectrum experiment, and electron spin resonance experiment to study the change of oxygen functional group content in coal caused by mechanochemical effect and its influence on coal spontaneous combustion. Yin et al [8] studied the effect of coal order on the free radical concentration of samples during the heating process and found that brown coal had the highest free radical concentration during the heating process and the strongest tendency to autoignition. Cai [9] found the opposite trend of absolute increment of free radical concentration with the tendency of coal autoignition by in situ coal low-temperature oxidation EPR study and proposed the relative growth rate of stable free radicals with low-temperature oxidation to determine the oxidative of coal with different degrees of deterioration.…”
Section: Introducementioning
confidence: 99%